Positive electrode active material and preparation method thereof, positive electrode sheet, battery and electrical equipment

By optimizing the sintering process and structure of high-nickel ternary cathode material, the problem of unstable structure of the material during charging and discharging is solved, and a longer cycle life and better battery performance is achieved.

CN118335898BActive Publication Date: 2025-02-07BEIJING EASPRING MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410545370.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-30
Publication Date
2025-02-07
Estimated Expiration
2044-04-30

AI Technical Summary

Technical Problem

The structure of the high-nickel ternary cathode material is unstable during the charging and discharging process, resulting in poor circulation performance and reduced safety.

Method used

The structural stability of the positive electrode active material is optimized by adjusting the sintering curve, controlling the particle size and structural morphology, coating, doping and single crystallization. The specific method includes a three-stage sintering process, optimizing the sintering conditions of the material intermediate and forming a cladding layer on the surface of the material.

Benefits of technology

It improves the structural stability of the positive electrode active material during multiple charge and discharge, extends the cycle life of the battery, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004825043410000031
    Figure BDA0004825043410000031
  • Figure BDA0004825043410000151
    Figure BDA0004825043410000151
  • Figure BDA0004825043410000152
    Figure BDA0004825043410000152
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium-ion batteries, and in particular to a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. The deviation angle of the (104) diffraction peak of the positive electrode active material is α n m ; Wherein, n is the number of charging cycles of the battery including the positive electrode active material, and n is an integer; m% is the percentage of the charging capacity to the total capacity of the battery when the battery is charged for the nth cycle; α n m When the battery is charged for the nth cycle and the percentage of the charging capacity to the total capacity of the battery is m%, the 2θ value corresponding to the (104) diffraction peak in the XRD diffraction spectrum of the positive electrode active material; the α n m Satisfaction: α 100 50 ‑α 100 0≤0.250°; α 100 100 ‑α 100 0≤1.500°. The positive electrode active material can remain stable during multiple charge and discharge processes, and the battery containing the positive electrode active material has a long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a positive electrode active material and a preparation method thereof, a positive electrode sheet, a battery and an electrical device. Background Art

[0002] At present, lithium-ion batteries are one of the most advanced rechargeable batteries to date. Since Sony introduced its technology to the market in 1991, lithium-ion batteries have been widely used in mobile phones, laptops, new energy vehicles and other fields. As the core component of batteries, the research and development of electrode materials has been driving the continuous development and progress of lithium-ion batteries. Compared with negative electrode materials, positive electrode materials are the most important factor affecting battery performance. They directly determine the capacity and cycle performance of lithium-ion batteries. Therefore, if you want to further improve the safety performance and specific energy of batteries, you must develop better positive electrode materials to match them.

[0003] As one of the core contents of the development of lithium-ion battery cathode materials, the continuous optimization and innovation of ternary materials is of great significance to the improvement of the endurance of new energy vehicles. x Co y M 1-x-y O2 (M is Mn or Al), which is divided into NCM and NCA according to the different metal elements M. Among them, the ternary material NCM has the advantages of cobalt and manganese incorporation, and to a certain extent makes up for their respective shortcomings. It has the advantages of high specific capacity, good rate performance, low cost, and low environmental pollution. Therefore, it has become one of the mainstream choices for battery positive electrode materials and is widely developed and applied. Specifically, it has the crystal structure of α-NaFeO2 and the R3m space group. With the change of the composition ratio of Ni, Co, and Mn, many properties of the material such as capacity and safety performance can be controlled to a certain extent. They are usually named according to the proportion of the material, such as 111 / 442 / 622 (representing the proportion of Ni, Mn, and Co, respectively). With the market demand and the deepening of research, the composition ratio of Ni, Co, and Mn gradually tends to high Ni and low Co and Mn, and ternary materials with a Ni ratio of more than 80% or even 90% have gradually become the mainstream of the market. While high nickelization brings higher energy density, it also exposes more problems, such as poor cycle performance and reduced safety caused by unstable material structure after charge and discharge cycles. As the Ni content increases, the instability problem in the crystal structure is also magnified, especially the phenomenon of Li / Ni mixed occupation frequently occurs in high-nickel ternary materials. 2+ The ionic radius (0.069nm) is similar to that of Li + (0.076nm) ion radius is similar, and the migration energy barrier of nickel ions is very low, resulting in Ni 2+ Very easy to move to Li+ Sites. This exists during the synthesis stage of the ternary material and during the charge and discharge process. Severe lithium-nickel mixing will affect the deintercalation and electrochemical performance of lithium ions. This structural defect will increase the internal resistance of the material, reduce the electrochemical activity, and reduce the cycle performance. However, at the same time, with appropriate Li / Ni mixing, the Ni atoms mixed into the Li layer can interact with O atoms, which helps stabilize the material structure. At the same time, during the repeated charge and discharge process, the original layered structure of the material changes with the Li + Due to the repeated insertion and removal of the transition metal ions, the interaction between the transition metal ions and the oxygen layer changes due to the changes in the Li layer and the transition metal valence state. The Li layer cannot return to its original state before and after charging and discharging, resulting in an irreversible change in the relative position of the transition metal layer and the oxygen layer. With the increase in the number of charge and discharge times, this change will gradually deepen, so the material structure itself has a profound impact on the stability of the transition metal layer and the life of the material. The change of this material structure with charging and discharging will also be intuitively reflected in the XRD characterization. The

[104] peak representing the hexagonal structure and the cubic structure will shift to the right with the release of lithium, and when lithium returns to the lithium layer, the

[104] peak position will move to the initial position, but with the structural changes brought about by the lithium-nickel mixing, it cannot return to the initial position.

[0004] In order to solve the above problems, the main improvement methods currently used include adjusting the sintering curve to control the particle size, structure and morphology, coating, doping and single crystallization. In existing research and inventions, doping is often used to enhance the strength of the particles themselves, or coating is used to limit the direct contact between the electrolyte and the positive electrode material, or the above purpose is achieved directly through single crystallization. However, as the market drives the rapid development of high nickel, the lithium-nickel mixed occupancy of the material itself and the large amount of lithium-nickel mixed arrangement during the cycle have become important factors restricting the development of high nickel ternary. Traditional modification methods are slightly weak for improving the performance of high nickel ternary. Therefore, further optimization based on the synthesis process of the material itself is more important. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present invention provides a positive electrode active material and a preparation method thereof, aiming to solve the problem that the positive electrode material structure is unstable and the cycle life is short during the charge and discharge process of the battery containing the positive electrode active material.

[0006] To this end, the first aspect of the present invention provides a positive electrode active material, wherein the deviation angle of the (104) diffraction peak of the positive electrode active material is α n m ;

[0007] Wherein, n is the number of charging cycles of the battery including the positive electrode active material, and n is an integer;

[0008] m% is the percentage of the charging capacity to the total capacity of the battery when the battery is charged for the nth cycle;

[0009] α n m When the battery is charged for an nth cycle and the percentage of the charging capacity to the total capacity of the battery is m%, the 2θ value corresponding to the (104) diffraction peak in the XRD diffraction spectrum of the positive electrode active material;

[0010] The α n m satisfy:

[0011] α 100 50 -α 100 0≤0.250°;

[0012] α 100 100 -α 100 0≤1.500°.

[0013] The present invention uses the parameter (104) diffraction peak deviation angle α n m To directly reflect Li + The reversibility of the structure of the positive electrode active material during insertion and extraction and the reversibility of the structure of the positive electrode active material during insertion and extraction of Li + When the positive electrode active material α n m When the above conditions are met, that is, the positive electrode active material can remain stable during multiple charge and discharge processes, the cycle life of the battery containing it is longer.

[0014] According to an embodiment of the present invention, the height change value ΔS of the transition metal layer in the positive electrode active material (TMO2) satisfy:

[0015] Among them, ΔS (TMO2) =S (TMO2) 0 -S (TMO2) 1 ;

[0016] ΔS (TMO2) is a change in the height of the transition metal layer in the positive electrode active material of a battery including the positive electrode active material before the battery is fully charged for the first time and before charging;

[0017] S (TMO2) 1 is the height of the transition metal layer in the positive electrode active material when the battery comprising the positive electrode active material is fully charged for the first time;

[0018] S (TMO2) 0It is the height of the transition metal layer in the positive electrode active material before the battery comprising the positive electrode active material is charged for the first time.

[0019] According to an embodiment of the present invention, the height change value ΔS of the transition metal layer in the positive electrode active material (TMO2) satisfy:

[0020] According to an embodiment of the present invention, the height change value ΔS of the transition metal layer in the positive electrode active material (TMO2) satisfy:

[0021] According to an embodiment of the present invention, the positive electrode active material further satisfies at least one of the following conditions:

[0022] The α n m Satisfaction: α 100 0-α 1 0≤0.750°;

[0023] The peak intensity ratio of the (003) diffraction peak to the (104) diffraction peak in the intrinsic XRD diffraction spectrum of the positive electrode active material is (003) / I (104) 1.20-1.60;

[0024] In the intrinsic XRD diffraction spectrum of the positive electrode active material, when the 2θ value is 43-46°, the half-peak width of the corresponding peak is ψ, and the ψ satisfies: 0.230°≤ψ≤0.260°;

[0025] The median particle size D of the positive electrode active material 50 , the D 50 Satisfy: 0.8μm≤D 50 ≤14.2μm.

[0026] According to an embodiment of the present invention, the positive electrode active material includes a lithium-containing metal oxide, and the lithium-containing metal oxide has a chemical formula shown in formula (1):

[0027] Li a Ni x Co y Mn z M b O2 (1)

[0028] Among them, 0.9≤a≤1.2, 0.3≤x<0.99, 0.01≤y≤0.5, 0.01≤z≤0.5, 0≤b≤0.2;

[0029] M is selected from at least one of Al, Zr, Y, Ti, Nb, Cr, Er, Mg, Ba, V, Sr, Ta, Mo, W, and Ce.

[0030] According to an embodiment of the present invention, the positive electrode active material further includes a coating layer, and the coating layer is disposed on the surface of the lithium-containing metal oxide.

[0031] According to an embodiment of the present invention, the coating layer includes an oxide containing at least one element of Al, B, Si, W, Ti, and Ce.

[0032] A second aspect of the present invention provides a method for preparing a positive electrode active material, the method comprising:

[0033] (1) mixing a positive electrode active material precursor, a lithium source and a first dopant, and performing a first sintering to obtain a positive electrode active material intermediate 1;

[0034] (2) mixing the positive electrode active material intermediate 1 with a second dopant, and performing a second sintering to obtain a positive electrode active material intermediate 2;

[0035] (3) The positive electrode active material intermediate 2 is mixed with a coating agent and subjected to a third sintering to obtain the positive electrode active material.

[0036] The preparation method is a three-stage sintering process to optimize the structural stability of the positive electrode active material itself and ensure that the initial mixed position of the positive electrode active material is within a certain range. At the same time, the (104) diffraction peak deviation angle α of the positive electrode active material and the transition metal layer height change value S (TMO2) This further demonstrates the performance optimization after the lithium-nickel mixing is reduced during the cycle.

[0037] According to an embodiment of the present invention, the first sintering conditions include: sintering at a temperature of T1 for 1.5-3 hours, heating to a temperature of T2 for 8-12 hours, and sintering in an oxygen atmosphere;

[0038] Wherein, the T1 is 300-500°C, the T2 is 650-1100°C, and the flow rate of the oxygen is 150-200L / (L·h).

[0039] According to an embodiment of the present invention, the second sintering conditions include: sintering at a temperature of T3 for 6-8 hours, with an oxygen atmosphere;

[0040] Wherein, the T3 satisfies: T2-50×(1.9-n)≤T3≤T2-50×(1.1-n), n is the ratio of the total molar amount of the doped metal element in the second dopant to the total molar amount of Ni, Co, and Mn elements in the positive electrode active material precursor; the flow rate of the oxygen is 150-200L / (L·h).

[0041] According to an embodiment of the present invention, the third sintering conditions include: sintering at 270-350° C. for 6-12 hours.

[0042] According to an embodiment of the present invention, the positive electrode active material precursor is a nickel-cobalt-manganese positive electrode material precursor.

[0043] According to an embodiment of the present invention, the lithium source is selected from one of lithium hydroxide, lithium hydroxide, lithium carbonate and lithium acetate.

[0044] According to an embodiment of the present invention, the first dopant and the second dopant are independently selected from one of carbonates, hydroxides, oxides and acetates that can provide at least one element among Al, Zr, Y, Ti, Nb, Cr, Er, Mg, Ba, V, Sr, Ta, Mo, W and Ce.

[0045] According to an embodiment of the present invention, the coating agent is selected from oxides capable of providing at least one element among Al, B, Si, W, Ti and Ce.

[0046] According to an embodiment of the present invention, the positive electrode active material has a chemical formula shown in formula (2):

[0047] Li a Ni x Co y Mn z M b O2@M'(2)

[0048] Among them, 0.9≤a≤1.2, 0.3≤x<0.99, 0.01≤y≤0.5, 0.01≤z≤0.5, 0≤b≤0.2;

[0049] M is selected from at least one of Al, Zr, Y, Ti, Nb, Cr, Er, Mg, Ba, V, Sr, Ta, Mo, W, and Ce;

[0050] M' is at least one element among Al, B, Si, W, Ti, Ce, and is coated on the matrix Li a Ni x Co y Mn z M b O2 surface.

[0051] A third aspect of the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the positive electrode active material described in the first aspect or the positive electrode active material prepared by the preparation method described in the second aspect.

[0052] The fourth aspect of the present invention provides a battery, the battery comprising the positive electrode sheet of the third aspect, so that the battery has excellent cycle performance.

[0053] A fifth aspect of the present invention provides an electrical device, wherein the electrical device comprises the battery described in the fourth aspect.

[0054] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION

[0055] The following embodiments of the technical solution of the present invention are described in detail. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and cannot be used to limit the protection scope of the present invention.

[0056] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0057] "Scope" disclosed in the present invention is defined in the form of lower limit and upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a particular range. The scope defined in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a particular parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3,4 and 5 are listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present invention, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0058] If not otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form a new technical solution.

[0059] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.

[0060] If not otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0061] The first aspect of the present invention provides a positive electrode active material, wherein the deviation angle of the (104) diffraction peak of the positive electrode active material is α n m ;

[0062] Wherein, n is the number of charging cycles of the battery including the positive electrode active material, and n is an integer;

[0063] m% is the percentage of the charging capacity to the total capacity of the battery when the battery is charged for the nth cycle;

[0064] α n m When the battery is charged for an nth cycle and the percentage of the charging capacity to the total capacity of the battery is m%, the 2θ value corresponding to the (104) diffraction peak in the XRD diffraction spectrum of the positive electrode active material;

[0065] The α n m satisfy:

[0066] α n 50 -α n 0≤0.250°;

[0067] α n 100 -α n 0≤1.500°;

[0068] The existing technology mostly uses high-nickel ternary cathode materials, but this crystal structure has the problem of instability, especially the phenomenon of Li / Ni mixed occupation frequently occurs in high-nickel ternary cathode materials. At the same time, during the repeated charge and discharge process of high-nickel ternary cathode materials, the original layered structure of the material changes with the Li +Due to repeated insertion and extraction, the interaction force between the transition metal ion layer and the oxygen layer changes due to the changes in the Li layer and the change in the valence state of the transition metal, and the Li layer cannot return to its original state before and after charging and discharging, resulting in an irreversible change in the relative position of the transition metal layer and the oxygen layer. As the number of charge and discharge times increases, this change will gradually deepen, so the stability of the transition metal layer and the life of the material are greatly affected by the structure of the material itself. The changes in the structure of the positive electrode material with charging and discharging will also be intuitively reflected in the XRD characterization. The (104) peak representing the hexagonal structure and the cubic structure will shift to the right as lithium is removed, and when lithium returns to the lithium layer, the (104) peak position will move to the initial position, but with the structural changes caused by the lithium-nickel mixing, it cannot return to the initial position. Therefore, by testing the (104) diffraction peak offset angle α of the positive electrode active material n m It can directly reflect the structural stability and electrochemical cycle performance strength of the material during the cycle process. n m Satisfy at least one of the following conditions: 100 50 -α 100 0≤0.250°; α 100 100 -α 100 When 0≤1.500°, it means that the material has better structural stability and better cycle performance.

[0069] According to a specific embodiment of the present invention, the (104) diffraction peak shift angle α n m Where n is the number of charging cycles of the battery including the positive electrode active material. The value of n is not particularly limited and can be selected by those skilled in the art according to actual needs. n is generally an integer of 0 to 100, excluding 0. As some specific examples, n is 1, 50, 100, etc.

[0070] According to a specific embodiment of the present invention, m% is the percentage of the charging capacity to the total capacity of the battery when the battery is charged for the nth round, and the value of m is generally 0 to 100. As some specific examples, m is 0, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, etc.

[0071] According to a specific embodiment of the present invention, α n mThat is, when the battery is charged for the nth cycle and the percentage of the charging capacity to the total capacity of the battery is m%, the 2θ value corresponding to the (104) diffraction peak in the XRD diffraction spectrum of the positive electrode active material, that is, the horizontal coordinate corresponding to the (104) diffraction peak in the XRD diffraction spectrum. Among them, the (104) diffraction peak position in the XRD diffraction spectrum of the positive electrode active material is generally between [43°, 49°], so the value of α is also the 2θ value corresponding to the highest peak with the horizontal coordinate in [43°, 49°] in the XRD diffraction spectrum of the positive electrode active material.

[0072] According to a specific embodiment of the present invention, the (104) diffraction peak shift angle α of the positive electrode active material n m It can be obtained through XRD diffraction experiment, and the test method is not particularly limited. Those skilled in the art can select it according to actual needs. For example, the positive electrode active material is prepared into a lithium ion battery according to a conventional method, and the positive electrode active material is fully charged and discharged at a current of 1C at 45°C for the n-1th week, and then charged to m%, and the positive electrode active material is tested by XRD diffractometer for the full spectrum. Among them, the XRD diffractometer test conditions are also not particularly limited. Those skilled in the art can select it according to actual needs. For example, the test conditions are: working temperature: 21±5°C, humidity: ≤65%; cooling water circulation machine: temperature: 23±1°, water pressure: 0.36MPa; refrigerant high pressure: 0.8-1.8MPa, refrigerant low pressure: 0.4-0.7MPa; scanning speed (Scanspeed) 5° / min; starting angle: 10.0000, ending angle: 90.0000; SamplingW: 0.0200; automatic rotating table speed: 60° / min, etc.

[0073] According to an embodiment of the present invention, the (104) diffraction peak shift angle α of the positive electrode active material is n m Further satisfy α 100 0-α 1 When 0≤0.750°, it indicates that the positive electrode active material has better structural stability and cycle performance.

[0074] According to a specific embodiment of the present invention, the height change value ΔS of the transition metal layer in the positive electrode active material (TMO2) satisfy:

[0075] Among them, ΔS (TMO2) =S (TMO2) 0 -S (TMO2) 1 ;

[0076] ΔS (TMO2)is a change in the height of the transition metal layer in the positive electrode active material of a battery including the positive electrode active material before the battery is fully charged for the first time and before charging;

[0077] S (TMO2) 1 is the height of the transition metal layer in the positive electrode active material when the battery comprising the positive electrode active material is fully charged for the first time;

[0078] S (TMO2) 0 It is the height of the transition metal layer in the positive electrode active material before the battery comprising the positive electrode active material is charged for the first time.

[0079] The height of the transition metal layer in the positive electrode active material refers to the distance between the transition metal layer and the adjacent oxygen layer in the crystal structure of the positive electrode active material. The height of the transition metal layer affects the structural stability of the positive electrode active material, the ability to embed and extract lithium ions, the electrochemical performance and safety, etc. When the change value of the transition metal layer height in the positive electrode active material is too large, it is determined that the material cannot remain stable during multiple charge and discharge processes, and the material life will be greatly shortened. When the change value of the transition metal layer height in the positive electrode active material meets the above conditions, it indicates that the structure of the positive electrode active material itself is not suitable for Li + Better stability during removal.

[0080] Specifically, ΔS (TMO2) The formula ΔS (TMO2) =S (TMO2) 0 -S (TMO2) 1 Calculated. Where S (TMO2) 1 is the height of the transition metal layer in the positive electrode active material when the battery is first charged to a fully charged state, S (TMO2) 0 is the initial transition metal layer height of the positive electrode active material, that is, the intrinsic transition metal layer height of the positive electrode active material. The size and change of the transition metal layer height can be measured by XRD and other techniques, that is, S (TMO2) 1 With S (TMO2) 0 Both can be obtained by conducting XRD diffraction tests on the corresponding positive electrode active materials and combining them with XRD refinement calculations.

[0081] Specifically, S (TMO2) 1 When a battery containing positive electrode active materials is charged to full charge at 1C for the first time, an XRD diffraction test is performed on the positive electrode materials, and the height of the transition metal layer in the positive electrode active materials is obtained by refinement. (TMO2) 0Before charging the battery containing the positive electrode active material for the first time, the positive electrode active material is subjected to an XRD diffraction test, and the transition metal layer height is obtained by refinement. The preparation of the battery containing the positive electrode active material can be selected by a conventional preparation method and is not particularly limited. The refinement process can be performed by a Rietveld full spectrum fitting refinement method, etc. The corresponding XRD test conditions are also not particularly limited, and those skilled in the art can select them according to actual needs, for example, the test conditions are different from the aforementioned (104) diffraction peak offset angle α n m The same are: working temperature: 21±5℃, humidity: ≤65%; cooling water circulation machine: temperature: 23±1°, water pressure: 0.36MPa; refrigerant high pressure: 0.8-1.8MPa, refrigerant low pressure: 0.4-0.7MPa; scanning speed (Scanspeed): 5° / min; starting angle: 10.0000, ending angle: 90.0000; SamplingW: 0.0200; automatic rotating table speed: 60° / min, etc.

[0082] According to a specific embodiment of the present invention, the height change value ΔS of the transition metal layer in the positive electrode active material (TMO2) satisfy: Preferably This indicates that the structure of the positive electrode active material is more stable during the charge and discharge process.

[0083] According to a specific embodiment of the present invention, the positive electrode active material further satisfies at least one of the following conditions:

[0084] The α n m Satisfaction: α 100 0-α 1 0≤0.750°. This indicates that the structure of the positive electrode active material is more stable during the charge and discharge process;

[0085] The peak intensity ratio of the (003) diffraction peak to the (104) diffraction peak in the intrinsic XRD diffraction spectrum of the positive electrode active material is (003) / I (104) is 1.20-1.60. This indicates that the degree of lithium-nickel mixing in the positive electrode active material is low. The intrinsic XRD diffraction pattern of the positive electrode active material should be understood as the diffraction pattern obtained by performing an XRD test on the positive electrode active material before the battery containing the positive electrode active material is charged for the first time;

[0086] In the intrinsic XRD diffraction spectrum of the positive electrode active material, when the 2θ value is 43-46°, the half-peak width of the corresponding peak is ψ, and the ψ satisfies: 0.230°≤ψ≤0.260°, which indicates that the positive electrode active material has a better degree of crystallinity.

[0087] The median particle size D of the positive electrode active material 50 , the D 50 Satisfy: 0.8μm≤D 50 ≤14.2μm. This indicates that the positive electrode active material has good cycle performance.

[0088] According to an embodiment of the present invention, the positive electrode active material includes a lithium-containing metal oxide, and the lithium-containing metal oxide has a chemical formula shown in formula (1):

[0089] Li a Ni x Co y Mn z M b O2(1)

[0090] Among them, 0.9≤a≤1.2, 0.3≤x<0.99, 0.01≤y≤0.5, 0.01≤z≤0.5, 0≤b≤0.2;

[0091] M is selected from at least one of Al, Zr, Y, Ti, Nb, Cr, Er, Mg, Ba, V, Sr, Ta, Mo, W, and Ce.

[0092] The positive electrode active material can achieve good structural stability during the cycle process, so that the battery containing the positive electrode active material has good cycle performance.

[0093] Specifically, the positive electrode active material may have a chemical formula as shown in formula (2):

[0094] Li a Ni x Co y Mn z M b O2@M'(2)

[0095] Among them, 0.9≤a≤1.2, 0.3≤x<0.99, 0.01≤y≤0.5, 0.01≤z≤0.5, 0≤b≤0.2;

[0096] M is selected from at least one of Al, Zr, Y, Ti, Nb, Cr, Er, Mg, Ba, V, Sr, Ta, Mo, W, and Ce;

[0097] M' is at least one element among Al, B, Si, W, Ti, Ce, and is coated on the matrix Li a Ni x Co y Mn z M bO2 surface. That is, the positive electrode active material may include a doped nickel-cobalt-manganese active material and a coating layer on at least part of its surface, so that the positive electrode active material has good structural stability and good resistance to electrolyte corrosion. The coating layer includes an oxide containing at least one element of Al, B, Si, W, Ti, and Ce. In addition, the positive electrode active material includes secondary particles, which are agglomerated by primary particles.

[0098] A second aspect of the present invention provides a method for preparing the above-mentioned positive electrode active material, the preparation method comprising:

[0099] (1) A positive electrode active material precursor, a lithium source and a first dopant are mixed and subjected to a first sintering to obtain a positive electrode active material intermediate 1.

[0100] According to a specific embodiment of the present invention, the first sintering conditions include: sintering at a temperature T1 for 1.5-3 hours, heating to a temperature T2 for 8-12 hours, and sintering in an oxygen atmosphere.

[0101] Wherein, the T1 is 300-500°C, for example, 300°C, 400°C, 500°C, etc.; the sintering time at this temperature can be 1.5-3h, for example, 1.5h, 2h, 2.5h, 3h, etc. The T2 is 650-1100°C, for example, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, etc.; the sintering time at this temperature can be 8-12h, for example, 8h, 9h, 10h, 11h, 12h, etc. The flow rate of the oxygen is 150-200 L / (L·h), for example, 150 L / (L·h), 160 L / (L·h), 170 L / (L·h), 180 L / (L·h), 190 L / (L·h), 200 L / (L·h), etc. The flow rate of oxygen in this specification refers to the volume of oxygen introduced into the unit volume of the container per unit time, and the unit is L / (L·h).

[0102] Specifically, the first sintering process may include: a pre-sintering treatment at 300-500°C for 1.5-3h at a constant temperature or with a regular temperature change, for example, heating to 400°C at a heating rate of 1-10°C / s and then pre-treating at a constant temperature for 3h, or heating from room temperature to 400°C at a uniform rate for 3h; the second stage is a constant temperature (650-1100°C) calcination lithiation stage for 8-12h.

[0103] According to a specific embodiment of the present invention, the positive electrode active material precursor is a nickel-cobalt-manganese positive electrode material precursor. At the same time, the preparation method is not particularly limited and does not affect the subsequent preparation of the positive electrode active material. Those skilled in the art can make a selection according to the actual situation, for example, a mixed salt solution of nickel salt, cobalt salt and manganese salt, a precipitant and a complexing agent solution are prepared according to the set molar ratio, and are respectively introduced into the reactor, and the reaction is carried out by controlling the ammonia concentration, reaction temperature, stirring speed, pH, etc. After the reaction is completed, the positive electrode active material precursor is obtained after aging, separation, washing and drying. There are no special restrictions on the types of nickel salt, cobalt salt, manganese salt, precipitant and complexing agent. Those skilled in the art can flexibly select according to the actual situation, for example, nickel salt, cobalt salt, manganese salt include but are not limited to the sulfate form; precipitant include but are not limited to the selection of sodium hydroxide; complexing agent include but are not limited to the selection of ammonia water. Similarly, the selection of ammonia concentration, reaction temperature, stirring speed, and pH can also be reasonably selected according to the preparation situation, for example, the ammonia concentration is 2-8g / L; the reaction temperature is 60-80℃; the stirring speed is 400-800rpm / min; the pH is 10-12, etc.

[0104] According to a specific embodiment of the present invention, the specific type of the lithium source is not particularly limited, and those skilled in the art may select it according to actual conditions. For example, the lithium source may include at least one of lithium hydroxide, lithium hydroxide, lithium carbonate, and lithium acetate.

[0105] According to a specific embodiment of the present invention, the specific type of the first dopant is not particularly limited, and those skilled in the art can select it according to actual needs. As some preferred schemes, the first dopant includes but is not limited to at least one of carbonates, hydroxides, oxides and acetates that can provide at least one element among Al, Zr, Y, Ti, Nb, Cr, Er, Mg, Ba, V, Sr, Ta, Mo, W and Ce.

[0106] (2) The positive electrode active material intermediate 1 and the second dopant are mixed and subjected to a second sintering to obtain a positive electrode active material intermediate 2.

[0107] According to a specific embodiment of the present invention, the second sintering conditions include: sintering at a temperature of T3 for 6-8 hours, for example, 6 hours, 7 hours, 8 hours, etc., and the sintering atmosphere is oxygen;

[0108] Wherein, the T3 satisfies: T2-50×(1.9-n)≤T3≤T2-50×(1.1-n), and n is the ratio of the total molar amount of the doped metal element in the second dopant to the total molar amount of Ni, Co, and Mn elements in the positive electrode active material precursor. The flow rate of the oxygen is 150-200 L / (L·h), for example, it can be 150 L / (L·h), 160 L / (L·h), 170 L / (L·h), 180 L / (L·h), 190 L / (L·h), 200 L / (L·h), etc.

[0109] In addition, the temperature T3 of this stage should not be too high. This process mainly involves doping the elements that can stabilize the structural characteristics of the material on the outside of the material in a more concentrated manner relative to the inside of the material to further stabilize the structure. Too high a temperature will cause the ions added in this process to be evenly dispersed. When the temperature is higher than the sintering temperature, it will cause excessive crystal growth, excessive crystallization, and more serious lithium-nickel mixing. If the temperature of the second sintering process is too low, the ions added in this process will be excessively concentrated on the surface, thereby affecting the material capacity or reducing the conductivity. It will also lead to insufficient reaction in this stage, and some of the main elements will be rearranged and enriched on the outside of the material and unable to re-phase in time, affecting the secondary sintering results.

[0110] Specifically, the second sintering process may include: heating to T3 at a heating rate of 3-8° C. / s, and maintaining the temperature for 6-8 hours.

[0111] According to a specific embodiment of the present invention, the specific type of the second dopant is not particularly limited, and it may be the same as or different from the first dopant in step (1). Those skilled in the art may select it according to actual needs. As some preferred schemes, the second dopant includes but is not limited to at least one of carbonates, hydroxides, oxides and acetates that can provide at least one element among Al, Zr, Y, Ti, Nb, Cr, Er, Mg, Ba, V, Sr, Ta, Mo, W and Ce.

[0112] According to a specific embodiment of the present invention, the ratio n of the total molar amount of the doping element in the second dopant to the total molar amount of Ni, Co, and Mn elements in the positive electrode active material precursor does not exceed 1.5 mol%, thereby stabilizing the surface structure of the material and achieving the effect of improving the stability of the material without affecting the capacity.

[0113] (3) The positive electrode active material intermediate 2 is mixed with a coating agent and subjected to a third sintering to obtain the positive electrode active material.

[0114] According to a specific embodiment of the present invention, the conditions of the third sintering include: at 270-350°C, for example, 270°C, 300°C, 330°C, 350°C, etc., and sintering for 6-12h, for example, 6h, 7h, 8h, 9h, 10h, 11h, 12h.

[0115] Specifically, the third sintering may be: uniformly heating the temperature to 270-350° C. at a heating rate of 2-5° C. / min at room temperature and sintering at a constant temperature for 6-12 hours to obtain the positive electrode active material.

[0116] According to a specific embodiment of the present invention, the specific type of the coating agent is not particularly limited, and those skilled in the art can select it according to actual needs. As some preferred schemes, the coating agent includes but is not limited to oxides that can provide at least one element among Al, B, Si, W, Ti, and Ce.

[0117] According to a specific embodiment of the present invention, the positive electrode active material has a chemical formula shown in formula (2):

[0118] Li a Ni x Co y Mn z M b O2@M'(2)

[0119] Among them, 0.9≤a≤1.2, 0.3≤x<0.99, 0.01≤y≤0.5, 0.01≤z≤0.5, 0≤b≤0.2;

[0120] M is selected from at least one of Al, Zr, Y, Ti, Nb, Cr, Er, Mg, Ba, V, Sr, Ta, Mo, W, and Ce;

[0121] M' is an element containing at least one of Al, B, Si, W, Ti, and Ce, and is coated on the matrix Li a Ni x Co y Mn z M b O2 surface.

[0122] The third aspect of the present invention provides a positive electrode plate, which includes the positive electrode active material described in the first aspect of the present invention or the positive electrode active material prepared by the method described in the second aspect.

[0123] The positive electrode sheet generally includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material.

[0124] The positive electrode current collector may be a conventional metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the positive electrode current collector may include at least one of copper foil, aluminum foil, nickel foil, stainless steel foil, stainless steel mesh, and carbon-coated aluminum foil.

[0125] The positive electrode active material includes the positive electrode active material described in the first aspect of the present invention or the positive electrode active material prepared by the method described in the second aspect.

[0126] The positive electrode active material layer may also optionally include a conductive agent and a binder. The conductive agent is used to improve the conductivity of the positive electrode active material layer, and the binder is used to firmly bind the positive electrode active material and the binder to the positive electrode current collector. The present invention does not specifically limit the types of the conductive agent and the binder, and they can be selected according to actual needs.

[0127] As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; the binder may include at least one of polyvinylidene fluoride (PVDF), vinylidene fluoride copolymers or their modified (for example, carboxylic acid, acrylic acid, acrylonitrile, etc.) derivatives.

[0128] These materials are all commercially available.

[0129] The fourth aspect of the present invention provides a battery, which comprises the positive electrode sheet according to the third aspect of the present invention, so that the battery has an excellent cycle life.

[0130] A battery is a battery that can be used again by recharging the active materials after discharge.

[0131] It is understandable that the battery proposed in the present invention is a lithium-ion battery.

[0132] Generally, a battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the charge and discharge process of the battery, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet to play a role of isolation. The electrolyte plays a role of conducting ions between the positive electrode sheet and the negative electrode sheet.

[0133] [Negative electrode]

[0134] In a battery, the negative electrode plate generally includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.

[0135] The negative electrode current collector is generally a structure or part that collects current. The negative electrode current collector can be any material in the art suitable for use as a negative electrode current collector for lithium secondary batteries, and can be a conventional metal foil or a composite current collector (for example, a metal material can be disposed on a polymer substrate to form a composite current collector). As an example, the negative electrode current collector can be a copper foil or a lithium sheet.

[0136] The specific type of the negative electrode active material is not limited, and active materials known in the art that can be used for the negative electrode of the battery can be used, and those skilled in the art can choose according to actual needs. As an example, the negative electrode active material can be a combination of one or more including but not limited to graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium. Among them, the graphite can be selected from a combination of one or more of artificial graphite, natural graphite and modified graphite; the silicon-based material can be selected from a combination of one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; the tin-based material can be selected from a combination of one or more of elemental tin, tin oxide compounds, and tin alloys. These materials can all be obtained through commercial channels.

[0137] In some embodiments, in order to further improve the energy density of the battery, the negative electrode active material may include a silicon-based material.

[0138] The negative electrode active material layer may also optionally include a binder, a conductive agent and other optional auxiliary agents.

[0139] As an example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0140] As an example, the binder may include one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB).

[0141] As examples, other optional additives may include thickening and dispersing agents (eg, sodium carboxymethylcellulose CMC-Na), and PTC thermistor materials.

[0142] [Electrolyte]

[0143] The electrolyte may include an electrolyte salt and a solvent.

[0144] As an example, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0145] As an example, the solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0146] In some embodiments, the electrolyte further includes additives, such as additives that may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.

[0147] [Isolation film]

[0148] As the above-mentioned isolation membrane, the present invention has no particular limitation and any known porous structure isolation membrane with electrochemical stability and mechanical stability can be selected according to actual needs, for example, it can include a combination of at least one of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.

[0149] The fifth aspect of the present invention provides an electric device, which includes the battery described in the fourth aspect. Specifically, the battery can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device can include but is not limited to mobile devices (such as mobile phones, laptops), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks), electric trains, ships and satellites, and energy storage systems.

[0150] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.

[0151] Example 1

[0152]

【Lithium Metal Oxide Li 1.03 Ni 0.896 Co 0.057 Mn 0.037 Al 0.008 W 0.001 Sr 0.001 O2, the coating layer contains B element positive electrode active material Li 1.03 Ni 0.896 Co 0.057 Mn 0.037 Al 0.008 W 0.001 Sr 0.001 Preparation of O2@B

[0153] (1) According to Li 1.03 Ni 0.896 Co 0.057 Mn 0.037 Al 0.008 W 0.001 Sr 0.001 Nickel sulfate salt, cobalt sulfate salt and manganese sulfate salt are mixed in a stoichiometric ratio of O2, dissolved in pure water to obtain a mixed salt solution A with a concentration of 2 mol / L, a sodium hydroxide solution with a concentration of 8 mol / L is prepared as a precipitant solution B, and an ammonia solution with a concentration of 6 mol / L is prepared as a complexing agent solution C; solutions A, B and C are added to the reactor from the liquid inlet pipe respectively, the ammonia concentration of the system is maintained at 6-8 g / L, the temperature of the reaction system is maintained at 60°C, the stirring speed is 600 rpm, and the pH of the reaction system is stabilized at 11.3. After the reaction is completed, the precursor material is obtained through aging, separation, washing and drying;

[0154] (2) The above precursor, lithium hydroxide, aluminum oxide, tungsten oxide, and strontium carbonate were weighed at a molar ratio of 0.99:1.03:0.002:0.001:0.001, mixed evenly in a mixer, and sintered at a constant temperature in an oxygen furnace with an oxygen flow rate of 500L / h. The specific process was to uniformly heat the room temperature for 3h to 300°C (T1), keep the temperature constant for 2h, then uniformly heat the room temperature for 6h to 780°C (T2), sinter at a constant temperature for 12h, and finally cool naturally. After cooling, crushing, and sieving, the positive electrode active material intermediate 1 was obtained;

[0155] (3) The above-mentioned positive electrode active material intermediate 1 is fully mixed with 0.002 molar ratio of aluminum oxide in a mixer, and sintered at a constant temperature in an oxygen furnace with an oxygen flow rate of 500L / h. The specific process is to uniformly heat the room temperature to 300°C for 3h, keep the temperature constant for 2h, then uniformly heat the room temperature to 650°C (T3) for 6h, sinter at a constant temperature for 8h, and finally cool naturally. After cooling, crushing and sieving, the positive electrode active material intermediate 2 is obtained;

[0156] (4) The positive electrode active material intermediate 2 and the boric acid powder material are placed in a high-speed mixer at a molar ratio of 1:0.01 and mixed evenly, and sintered at a constant temperature of 350° C. in an oxygen furnace for 10 hours. After cooling, sieving, and iron removal, the positive electrode active material is obtained.

[0157]

Preparation of positive electrode

[0158] The Li 1.03 Ni 0.896 Co 0.057 Mn 0.037 Al 0.008 W 0.001 Sr 0.001 9.5g of O2@B, 0.25g of acetylene black and 0.25g of polyvinylidene fluoride (PVDF) in N-methylpyrrolidone (NMP) solution were mixed to form a positive electrode slurry. The slurry was coated on aluminum foil and dried, and then stamped with a pressure of 100MPa to form a positive electrode sheet with a diameter of 12mm and a thickness of 120μm, and then dried in a vacuum drying oven at 120℃ for 12h.

[0159]

Preparation of negative electrode sheet

[0160] The negative electrode uses a Li metal sheet with a diameter of 17 mm and a thickness of 1 mm.

[0161]

Preparation of electrolyte

[0162] A 1.0 mol / L LiPF6 solution was used as the electrolyte, and an equal amount of a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) was used as the solvent.

[0163]

Isolation film

[0164] A polyethylene porous film with a thickness of 25 μm was used as the separator.

[0165] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then they are wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and the prepared electrolyte is injected into the dried secondary battery. After vacuum packaging, standing, formation, and shaping processes, a lithium-ion battery is obtained.

[0166] The lithium ion batteries containing positive electrode active materials of Examples 2-9 and Comparative Examples 1-5 are the same as Example 1 except for different parameters (see Table 1). The chemical formulas of the obtained positive electrode active materials are shown in Table 2.

[0167] Table 1

[0168]

[0169] In Table 1, “ / ” means no addition or none.

[0170] Table 2

[0171]

[0172]

[0173] Note: In Table 2, the chemical formula before @ represents the composition of lithium metal oxide in the positive electrode active material, and the chemical formula after @ represents the main element in the coating layer.

[0174] Testing and analysis:

[0175] 1. XRD tests were performed on the positive electrode active materials of Examples 1-9 and Comparative Examples 1-5, and the test results are shown in Table 3.

[0176] α 1 100 , α 1 50 , α 1 0.I (003) / I (104) , half-peak width ψ, ΔS (TMO2)Determination: All are measured by X-ray diffractometer (XRD), and the specific test conditions are: working temperature: 21±5℃, humidity: ≤65%; cooling water circulation machine: temperature: 23±1°, water pressure: 0.36MPa; refrigerant high pressure: 0.8-1.8MPa, refrigerant low pressure: 0.4-0.7MPa; scanning speed (Scanspeed): 5° / min; starting angle: 10.0000, ending angle: 90.0000; SamplingW: 0.0200; automatic rotating table speed: 60° / min. Among them, S was obtained by performing XRD diffraction test on the corresponding positive active material and combining XRD refinement calculation. (TMO2) 1 With S (TMO2) 0 , and then through the formula ΔS (TMO2) =S (TMO2) 1 -S (TMO2) 0 Calculate ΔS (TMO2) .

[0177] 2. The cycle performance of the lithium ion batteries of Examples 1-9 and Comparative Examples 1-5 were tested respectively. The test results are shown in Table 3.

[0178] Test method: Charge and discharge the battery sample twice at a current density of 20mA / g, with a cut-off voltage of 3.0-4.3V, and activation is completed. Use the activated battery sample to perform 100 charge and discharge cycles at a temperature of 45°C, a current density of 1C in a voltage range of 3.0-4.3V. The cycle performance of the battery sample is characterized by the high-temperature capacity retention rate, that is, the discharge specific capacity at the 100th cycle / initial discharge specific capacity × 100%.

[0179] Table 3

[0180]

[0181]

[0182] Result analysis:

[0183] (1) The positive electrode active materials in Examples 1-9 are all obtained by the preparation method provided by the present invention, and the corresponding α 100 50 -α 100 0 is less than 0.250°, α 100 100 -α 100 0 is less than 1.500°, α 100 0-α 1 0 is less than 0.750°, ΔS (TMO2) All less than I (003) / I (104) are all between 1.20 and 1.60, indicating that the material has good structural stability. + The stability during release is good, and the cycle life of the battery containing it is long;

[0184] (2) Comparative Example 1 is compared with Example 7. The doping element W is replaced with La. As shown in Table 3, the α n m The change value, ΔS (TMO2) ,I (003) / I (104) All of them are not within the scope of the present invention. At the same time, the capacity retention rate of the battery sample in Comparative Example 1 (89.6%) is also lower than that in Example 7 (91.5%), indicating that the selection of the doping element provided by the present invention is more conducive to the structural stability of the positive electrode active material and the cycle life of the battery containing it;

[0185] (3) Comparative Example 2 is compared with Example 1, in which the two-stage sintering in the first sintering process is changed to a one-stage sintering. As shown in Table 3, the α n m The change value, ΔS (TMO2) ,I (003) / I (104) All of them are not within the scope of the present invention. At the same time, the capacity retention rate of the battery sample in Comparative Example 2 (89.3%) is also lower than that in Example 1 (92.8%), indicating that the two-stage sintering in the first sintering process is more conducive to the structural stability of the positive electrode active material and the cycle life of the battery containing it;

[0186] (4) Comparative Example 3 is compared with Example 1, in which the second sintering process is omitted. As shown in Table 3, the α n m The change value, ΔS (TMO2) ,I (003) / I (104) All of them are not within the scope of the present invention. At the same time, the capacity retention rate of the battery sample in Comparative Example 3 (86.6%) is also lower than that in Example 1 (92.8%), indicating that combining the first sintering process with the second sintering process is more conducive to the structural stability of the positive electrode active material and the cycle life of the battery containing the same;

[0187] (5) Compared with Example 1, the sintering temperature of the second sintering process was lowered in Comparative Example 4. As shown in Table 3, the α n m Change value, ΔS, I (003) / I (104)All of them are not within the scope of the present invention. At the same time, the capacity retention rate of the battery sample in Comparative Example 4 (88.0%) is also lower than that in Example 1 (92.8%), indicating that combining the first sintering process with the second sintering process is more conducive to the structural stability of the positive electrode active material and the cycle life of the battery containing the same;

[0188] (6) Compared with Example 1, the sintering temperature of the second sintering process was increased in Comparative Example 5. As shown in Table 3, the α n m The change value, ΔS (TMO2) ,I (003) / I (104) All of them are not within the scope defined by the present invention. At the same time, the capacity retention rate of the battery sample in Example 5 (89.1%) is also lower than that in Example 1 (92.8%), indicating that selecting the temperature range defined by the present invention is more conducive to the structural stability of the positive electrode active material and the cycle life of the battery containing it.

[0189] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0190] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A positive electrode active material, characterized in that: α n m When the percentage of the charging capacity to the total capacity of the battery is m% during the nth cycle of battery charging, the 2θ value corresponding to the (104) diffraction peak in the XRD diffraction spectrum of the positive electrode active material; Wherein, n is the number of charging cycles of the battery including the positive electrode active material, and n is an integer; m% is the percentage of charging capacity to total battery capacity when the battery is charged for the nth cycle; The α n m satisfy: α 100 50 -α 100 0≤0.250°; α 100 100 -α 100 0≤1.500°; The positive electrode active material includes a lithium-containing metal oxide, and the lithium-containing metal oxide has a chemical formula shown in formula (1): Li a Ni x Co y Mr z M b O2 (1) Among them, 0.9≤a≤1.2, 0.3≤x<0.99, 0.01≤y≤0.5, 0.01≤z≤0.5, 0≤b≤0.2; M is selected from at least one of Al, Zr, Y, Ti, Nb, Cr, Er, Mg, Ba, V, Sr, Ta, Mo, W, and Ce; The positive electrode active material further includes a coating layer, and the coating layer is arranged on the surface of the lithium-containing metal oxide; The coating layer includes an oxide containing at least one element of Al, B, Si, W, Ti, and Ce.

2. The positive electrode active material according to claim 1, characterized in that The change value ΔS of the transition metal layer height in the positive electrode active material (TMO2) satisfy: Among them, ΔS (TMO2) =S (TMO2) 0 -S (TMO2) 1 ; ΔS (TMO2) is a change in the height of the transition metal layer in the positive electrode active material of a battery including the positive electrode active material before the battery is fully charged for the first time and before charging; S (TMO2) 1 is the height of the transition metal layer in the positive electrode active material when the battery comprising the positive electrode active material is fully charged for the first time; S (TMO2) 0 It is the height of the transition metal layer in the positive electrode active material before the battery comprising the positive electrode active material is charged for the first time.

3. The positive electrode active material according to claim 2, characterized in that The change value ΔS of the transition metal layer height in the positive electrode active material (TMO2) satisfy:

4. The positive electrode active material according to claim 2, characterized in that The change value ΔS of the transition metal layer height in the positive electrode active material (TMO2) satisfy:

5. The positive electrode active material according to claim 1, characterized in that The positive electrode active material also satisfies at least one of the following conditions: The α n m Satisfaction: α 100 0-α 1 0≤0.750°; The peak intensity ratio of the (003) diffraction peak to the (104) diffraction peak in the intrinsic XRD diffraction spectrum of the positive electrode active material is (003) / I (104) 1.20-1.60; In the intrinsic XRD diffraction spectrum of the positive electrode active material, when the 2θ value is 43-46°, the half-peak width of the corresponding peak is ψ, and the ψ satisfies: 0.230°≤ψ≤0.260°; The median particle size D of the positive electrode active material 50 , the D 50 Satisfy: 0.8μm≤D 50 ≤14.2μm.

6. A method for preparing a positive electrode active material according to any one of claims 1 to 5, characterized in that: The preparation method comprises: (1) mixing a positive electrode active material precursor, a lithium source and a first dopant, and performing a first sintering to obtain a positive electrode active material intermediate 1; (2) mixing the positive electrode active material intermediate 1 with a second dopant, and performing a second sintering to obtain a positive electrode active material intermediate 2; (3) mixing the positive electrode active material intermediate 2 with a coating agent and performing a third sintering to obtain the positive electrode active material; The first dopant and the second dopant are independently selected from one of carbonates, hydroxides, oxides and acetates that can provide at least one element among Al, Zr, Y, Ti, Nb, Cr, Er, Mg, Ba, V, Sr, Ta, Mo, W and Ce; The first sintering conditions include: sintering at a temperature of T1 for 1.5-3 hours, heating to a temperature of T2 and sintering for 8-12 hours; wherein T1 is 300-500° C., and T2 is 650-1100° C.; The second sintering conditions include: sintering at a temperature of T3 for 6-8 hours; the T3 satisfies: T2-50×(1.9-n)≤T3≤T2-50×(1.1-n), where n is the ratio of the total molar amount of the doped metal element in the second dopant to the total molar amount of Ni, Co, and Mn elements in the positive electrode active material precursor.

7. The preparation method according to claim 6, characterized in that: The first sintering atmosphere is oxygen; Wherein, the flow rate of the oxygen is 150-200 L / (L·h).

8. The preparation method according to claim 6, characterized in that: The second sintering atmosphere is oxygen; Wherein, the flow rate of the oxygen is 150-200 L / (L·h).

9. The preparation method according to claim 6, characterized in that: The third sintering conditions include: sintering at 270-350° C. for 6-12 hours.

10. The preparation method according to claim 6, characterized in that: The positive electrode active material precursor is a nickel-cobalt-manganese positive electrode material precursor.

11. The preparation method according to claim 6, characterized in that: The lithium source is selected from one of lithium hydroxide, lithium hydroxide, lithium carbonate and lithium acetate.

12. The preparation method according to claim 6, characterized in that: The coating agent is selected from oxides capable of providing at least one element among Al, B, Si, W, Ti and Ce.

13. A positive electrode sheet, characterized in that: The positive electrode sheet comprises the positive electrode active material according to any one of claims 1 to 5 or the positive electrode active material prepared by the preparation method according to any one of claims 6 to 12.

14. A battery, characterized in that: The battery comprises the positive electrode sheet according to claim 13.

15. An electrical equipment, characterized in that: Comprising the battery of claim 14.

Citation Information

Patent Citations

  • Positive electrode active material, positive electrode plate and lithium ion secondary battery

    CN112447964A

  • Blending type lithium ion battery positive electrode material, preparation method thereof and lithium ion battery

    CN115832241A